2013
DOI: 10.1089/thy.2011.0514
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism in Adult Male Rats Alters Posttranscriptional Mechanisms of Luteinizing Hormone Biosynthesis

Abstract: Hypothyroidism in adult male rats has dual effects on the pituitary testicular axis. It alters posttranscriptional mechanisms of LH synthesis and probably has a direct effect on testicular function. However, these data suggest the possibility that reduced LH bioactivity may account in part for impaired testicular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
2
17
0
2
Order By: Relevance
“…Thirty minutes after treatment with T 3 , the poly(A) tail length of Tshb mRNA of Tx rats was reduced to values similar to those observed in the poly(A) tail length of euthyroid rats and was positively correlated with a marked reduction in the content of Tshb in polysome fractions indicating that T 3 rapidly reduced mRNA translation and TSH protein synthesis (GoulartSilva et al 2011, Bargi-Souza et al 2013.…”
Section: Rapid and Negative Posttranscriptional Regulation Of Cga Andmentioning
confidence: 91%
See 4 more Smart Citations
“…Thirty minutes after treatment with T 3 , the poly(A) tail length of Tshb mRNA of Tx rats was reduced to values similar to those observed in the poly(A) tail length of euthyroid rats and was positively correlated with a marked reduction in the content of Tshb in polysome fractions indicating that T 3 rapidly reduced mRNA translation and TSH protein synthesis (GoulartSilva et al 2011, Bargi-Souza et al 2013.…”
Section: Rapid and Negative Posttranscriptional Regulation Of Cga Andmentioning
confidence: 91%
“…Using Tx rats, we observed that in hypothyroidism, the poly(A) tail length of Tshb mRNA is increased, followed by a significant rise in the translational rate of Tshb, besides the expected increase in the transcriptional process (Bargi-Souza et al 2013). Thirty minutes after treatment with T 3 , the poly(A) tail length of Tshb mRNA of Tx rats was reduced to values similar to those observed in the poly(A) tail length of euthyroid rats and was positively correlated with a marked reduction in the content of Tshb in polysome fractions indicating that T 3 rapidly reduced mRNA translation and TSH protein synthesis (GoulartSilva et al 2011, Bargi-Souza et al 2013.…”
Section: Rapid and Negative Posttranscriptional Regulation Of Cga Andmentioning
confidence: 91%
See 3 more Smart Citations